Quality Analysis of Digital Service Virtual Plasa Witel Samarinda Using e-Servqual Method - Khotijah, Syafitri; Widada, Dharma; Amelia Pawitra, Theresia (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
Virtual Plasa is a new digital service from PT. Telkom, released in 2020, with the intention of providing communication services from Telkom concisely. This study aims to determine the quality of service at Virtual Plasa, identify and evaluate the causes of the gap, and recommend improvement. The results show that Virtual Plasa services have a significant level of service quality. Even if the average expectation is higher than the average perception, the difference is modest, and the overall service is good. The Wilcoxon test results show that only two of eighteen attributes have a significant negative value, which is the website has a positive image and follow up on the website as promised. The attribute